Authoritarian reputation laundering in Paris and Lisbon - Cohen, C; Soares De Oliveira, R (National Endowment for Democracy, 2022)
Research on the financial and reputational dimensions of international kleptocracy largely focuses on the United States and United Kingdom, which draws attention away from other European, and increasingly Asian, financial centers that enable authoritarian reputation laundering. Paris and Lisbon are particularly informative case studies, where reputation service provision is considered mainstream and ties to former colonial networks have facilitated reputation laundering in different ways for authoritarian leaders and their families. Greater transparency is critical to addressing this challenge about which much remains unknown. Recommendations include creating a mandatory lobbying registry; requiring media, universities, and think tanks to report external funding; and scrutinizing political party financing.